2012
DOI: 10.1182/blood-2011-09-377713
|View full text |Cite
|
Sign up to set email alerts
|

Adult patients with acute lymphoblastic leukemia and molecular failure display a poor prognosis and are candidates for stem cell transplantation and targeted therapies

Abstract: Quantification of minimal residual disease (MRD) by real-time PCR directed to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
283
1
18

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 421 publications
(310 citation statements)
references
References 31 publications
8
283
1
18
Order By: Relevance
“…2 Most patients reach CR but still have evidence of persistent minimal residual disease (MRD) after induction and consolidation, and tend to relapse with time. 3,4 Efforts have been made to develop therapeutic procedures aimed at controlling/eradicating MRD. 5,6 Over the years, the anti-leukemic potential of natural killer (NK) cells and their ability to regulate normal and possibly neoplastic hematopoietic precursors has raised considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…2 Most patients reach CR but still have evidence of persistent minimal residual disease (MRD) after induction and consolidation, and tend to relapse with time. 3,4 Efforts have been made to develop therapeutic procedures aimed at controlling/eradicating MRD. 5,6 Over the years, the anti-leukemic potential of natural killer (NK) cells and their ability to regulate normal and possibly neoplastic hematopoietic precursors has raised considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…1 Blinatumomab, a bispecific T-cell engager (BiTE ® ) antibody construct with dual specificity for CD19 and CD3, 2 demonstrated efficacy in the treatment of relapsed or refractory B-lineage ALL in two phase 2 studies, with response rates of 43% to 69% and median RFS of 5.9 to 7.6 months.…”
mentioning
confidence: 99%
“…MRD after induction therapy is regarded as an independent predictor for survival in younger adults with ALL [32,33] and seems to be a powerful predictor for outcome in older adults [4]. Furthermore, Bassan and colleagues previously demonstrated that MRD status can assist in allocating adult patients in remission to maintenance or HSCT [34].…”
Section: Discussionmentioning
confidence: 99%